Implementasi Experiential Learning pada Materi Proses Pembentukan Urine Manusia - Nugroho, Manasye Viony Kasih; Nurandini , Anggelia (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2023)
Teaching aids in the learning process can help students understand the material being taught. The purpose of this study was to describe the interests and motivation of students after using teaching aids. The teaching aids were developed using the Borg & Gall research model which was limited to five stages, namely information gathering, planning, product draft development, initial field trials, and test results reports. This research was conducted on a small scale involving five students of class VIII. Students' interest in teaching aids is described when students enjoy using teaching aids as learning media, while student motivation is known that students' understanding of the process of forming human urine increases. The students' interest and motivation towards the use of teaching aids from the questionnaire obtained the highest scores of 100%, 96%, 92%, respectively, which indicates that the teaching aids are very good and have a positive influence on student motivation. The results of the small-scale research indicate that the teaching aids developed can attract students' interest and motivation to learn. This reflects the experiential learning process, especially in the material for the process of forming human urine. Keywords: teaching aids, urine formation process, Experiential Learning, motivation